DC Super Hero Girls. Hits and myths - Fontana, Shea (Superhero girls graphic novels., 2016)
'Intro to Epics' is one of Wonder Woman's favorite classes at DC Super Hero High, but even for an overachiever, balancing high school literature assignments with learning to be a superhero can be tough. But you know what they say about learning-experience is the best teacher! So when Wonder Woman, Batgirl, Supergirl, Bumblebee, Poison Ivy, Katana, and Harley Quinn fight a cyclops, a witch, and a bevy of sirens, they're sure to learn a thing or two about The Odyssey ... if they survive their epic battle in the underworld!